(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In recent years there has been a growing amount of research concerned with integrating mobile technologies for teaching and learning purposes. In spite of the rapid proliferation of the cell phone as an indispensable mobile tool in the lives of 21st century teachers and learners, it remains a banned item in many schools and (History) classrooms. As a result cell phone technology, such as its Short Message Service (SMS) texting function in combination with the Audience Response System (ARS), Poll Everywhere, has not been extensively explored as teaching and learning tools in the school classroom. The purpose of this article is to, through a small scale pilot study, explore and assess how the ARS, Poll Everywhere (www.polleverywhere.com), which is based on the cell phone’s SMS function, can be integrated into History lessons to support and enhance the teaching and learning experience of secondary school learners. The article furthermore aims to establish the perceptions and attitudes of History learners (n=52), as well as the experience of the teacher after having had a firsttime opportunity to integrate SMS technology and Poll Everywhere into their lessons. The results indicate among others that although most of the participants singled out data charges as the biggest possible hindrance to its utilisation, the overwhelming majority had positive perception levels about the integration of cell phone technology and the Poll Everywhere application into their History class. The experiences of the teacher who presented the lessons were positive as well as negative in nature.